Assessing the Welfare Impacts of Forest Ecosystem Service Management Policies and Their Distributional Rules - Dreoni, Ilda; Utila, Henri; Neil, Clive; Eigenbrod, Felix; Schaafsma, Marije (Frontiers in Forests and Global Change, 2022)
Community based management (CBM) is widely advocated as an effective method for governing and managing ecosystem services (ES). However, the distributional rules and maximum harvesting levels are likely to affect both the effectiveness of CBMs in maintaining ES and the fairness and equity of access to these ES. This paper proposes a methodological approach for investigating normative trade-offs involved in CBM of forests, where forest conservation objectives need to be traded off against livelihoods objectives. The study uses remote sensing methods to quantify forest ES supply in Namizimu Forest Reserve in Malawi, and links this to demand for ES within the villages near the reserve. It then investigates how a plausible set of CBM rules can be developed to cap consumption of forest products to sustainable amount and quantifies, by using monetary valuation techniques, how these set of rules may affect the total well-being of local population. Our results demonstrate that, due to the spatial mismatches between demand and supply, the distribution of provisioning ES to the population across the harvesting area is unequal in biophysical terms. The current available stock of forest products is sufficient to cover the current demand, however it is higher than the mean annual increment and will lead to forest degradation. The welfare analysis of co-management policies demonstrates that total societal welfare is maximized when 40% of biomass is distributed to the rich group while the remaining 60% is allocated to the poor group. However, this scenario does not maximize WTP in each sub-area of forest but just for those that have a high availability for biomass. When biomass availability is low, total societal welfare is maximized when more trees are distributed to richer users. Yet, a policymaker may choose a distributional rule that distribute more trees to the poor on normative grounds and forego the objective of maximizing total welfare. In such cases the WTP analysis outlined in this paper can support the policymaker in choosing the distributional rule that minimize trade-offs between efficiency, i.e., maximizing total welfare, and livelihoods objectives.